Sorry, can not see the full picture, try uploading the full image of the question.
Answer:
Step-by-step explanation:
y-y1 = m(x-x1)
y-4 = 2(x-3)
y-4=2x-6
y= 2x -6+4
y=2x-2
Answer:
2>x
y>-1
Step-by-step explanation:
assume y=0 when finding x and vice versa
Answer:
C. 490.
Step-by-step explanation:
25% = 0.25.
If the number of emails that Ryan and Taylor each received is x emails then Sara received 2x + 0.25 * 2x = 2.5 emails.
So 2x + 2.5x = 882
x = 882/4.5
x = 196.
So Sara received 2.5 * 196
= 490 emails.
Answer:
point!!!!!!!
Step-by-step explanation: